The Social Media and Religion – New Challenges - Drakulovska Chukaleska, Marija; Dragovikj, Anica (Faculty of Philosophy, Skopje, 2020)
In this paper we analyze the relationship between social media and religion. The subject of the research is to identify the power and the practical relevance of two spheres which are of utmost importance for more adequate understanding recent reality. According to Stewart Hoover ‘religion and media seem to be ever more connected as we move further into the twenty – first century’ (Hoover, 2006:1). Today, social media increasingly become part of our daily lives; people will find new ways to interact with religion and spirituality. The main goal is to explore the power of social media and attend to the ways in which these digital technologies are reconstituting and transforming the religious practices of the modern humans. Increasingly, people are religious or spiritual or inspired by religious texts, but only because they have chosen to plug in and engage with social media. The paper emphasizes the role of social media to represent a new challenge to individuals and institutions. This new challenge will create a networked religion, a networked community; convergent practice; and a multisite reality.
Keywords: social media, religion, changes, new challenge, network